POTENCY OF YEAST AS A BIOCONTROL AGENT OF OCHRATOXIN A-PRODUCING FUNGI AND ITS EFFECT ON ARABICA COFFEE TASTE - Okky S. Dharmaputra; Ina Retnowati; Nijma Nurfadila (SEAMEO BIOTROP, 2023)
Biocontrol agents can be used to control mycotoxigenic fungi, which include different species of yeast. The objectives of this research were to select yeast isolates that can inhibit the growth of ochratoxin A (OTA)-producing fungi (Aspergillus ochraceus BIO 37310) and to increase the taste of Arabica coffee processed using wet and semi-wet methods. Twenty-two yeast isolates (KA, KA2, KB, KB2, KC, KD, Endomyces decipiens BIO 131215, E. fibuliger BIO 132216, BIO 132217, BIO 13218, BIO 132219, BIO 132220, Candida krusei (= Issatchenkia orientalis) BIO 211285, BIO 211286, BIO 211287, BIO 211288, BIO 211289, BIO 211290, BIO 211291, Saccharomyces cerevisiae BIO 341363, BIO 341364, and BIO 341365) were screened for their antagonistic property against A. ochraceus BIO 37310 in vitro using well (dip) test method. The results showed that C. krusei (BIO 211287, BIO 211288, and BIO 211289) inhibited A. ochraceus BIO 37310. In vivo the highest yeast population was found in coffee beans processed using a semi-wet method inoculated with C. krusei BIO 211288 (46,222 Â± 9,576 cfu/g), which was not significantly different from that of the coffee beans inoculated with C. krusei BIO 211287 (36,333 Â± 14,000 cfu/g). The three yeast isolates were also able to grow either in coffee beans processed using wet or semi-wet methods inoculated with A. ochraceus BIO 37310 and each yeast isolate. Interaction between the three yeast isolates and A. ochraceus BIO 37310 resulted in E-type interaction, i.e. the fungus was not able to grow anymore, while the yeasts grew further. The total cupping scores of coffee beans inoculated with the three yeast isolates were higher than those of coffee beans uninoculated and inoculated with commercial lactic acid bacteria. The three yeast isolates could be used as biocontrol agents of A. ochraceus BIO 37310 and increase the sensorial quality of coffee beverages.